Karakteristik Edible Film Fungsional Pati Ganyong dengan Penambahan Filtrat Gambir (Uncaria gambir Roxb)dan Ekstrak Kenikir (Cosmos caudatus) - Reza Fahlevi; Budi Santoso; Gatot Priyanto (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2019)
Fahlevi R, Santoso B, Priyanto G. 2019. the Characteristic Of Edibel Film Fungtional Ganyong Starch with The Addition Of Gambir Filtrat (Uncaria gambir Roxb) and kenikir ectratct (Cosmos caudatus). In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang 4-5 September 2019. pp. 567-575. Palembang: Unsri Press. The objective research was to determine the effect of adding gambir extract (Uncaria gambir Roxb) and kenikir extract (Cosmos caudatus) on physical, chemical, and antibacterial of ganyong starch-based films. This reasearch used a Factorial Completely Randomized Design (RALF) with two treatment factors, namely factor A concentration of gambir extract and factor B concentration of kenikir extract. The observed parameters included physical analysis (thickness, elongation percent, compressive strength, and water vapor transmission rate), chemical analysis (total phenol), and analysis of antibacterial activity. The results showed that the treatment of the concentration of gambir extract had a significant effect on thickness, compressive strength, water vapor transmission rate, total phenol and antibacterial activity. The treatment of the concentration of kenikir extract addition to edible fim significantly affected on thickness, compressive strength, water vapor transmission rate, and total phenol. The interaction of the treatment of the addition of concentrations of gambir and kenikir are significantly affected on thickness and compressive strength of edible film. A2B2 treatment (gambir extract 2.5%: 2.5% kenikir extract) is the best treatment based on physical, chemical, and antibacterial characteristics of edible film. Keywords: edible film, gambir, kenikir